PENGARUH CITRA PERUSAHAAN DAN PELAYANAN TERHADAP KEPUASAAN SERTA DAMPAKNYA TERHADAP LOYALITAS (STUDI PADA HOTEL JEPARA INDAH) (Students' Journal of Economic and Management, 2013)
The purpose of this study was to analyze the effect  and analyze the influence of corporate image on customer satisfaction and service. To test and analyze the influence of corporate image, service and customer satisfaction on consumer loyalty. Populations used are guests staying in hotel Jepara Indah in 2012 is 23 390 peoples, the number of samples by using purposive sampling technique was 100 respondents. Types of data used are primary data, in the form of questionnaires. Tool using multiple regression analysis. The results are: Corporate image has an effect on customer satisfaction, with the positive direction of regression, meaning that if the image of the company increases, the customer satisfaction will increase. Services have an influence on customer satisfaction, with the positive direction of regression, meaning better service, then customer satisfaction will increase. Customer satisfaction has an influence on customer loyalty, with positive regression coefficients, if customer satisfaction is increasing, it will increase customer loyalty. Influential corporate image on customer loyalty with a positive regression direction, meaning that if the image of the company's increasing customer loyalty will increase. Services affect customer loyalty with regression toward the positive, it means if the service is getting better, then it will increase customer loyalty. Corporate image indirect effect on customer loyalty through customer satisfaction. With customer satisfaction as an intervening variable between the influence of corporate image on customer loyalty. Services directly influence customer loyalty through customer satisfaction. With customer satisfaction as an intervening variable between service influence on customer loyalty. Keywords: Corporate Image, Service, Customer Satisfaction, Customer Loyalty